Dalla cosa alla non-cosa: transizioni, archiviazioni e pratiche artistiche contemporanee (Mantichora. Italian Journal of Performance Studies, 2025)
“The earthly order, the planetary order, is made up of things that take on a lasting form and create a stable, habitable environment […] Today the earthly order is replaced by the digital order. The digital order derealizes the world by computerizing it” [Han 2022, p. 5]. Byung-Chul Han’s awareness, followed by the registration of infocracy as an established and dominant regime [Han 2023], also finds confirmation in the world of contemporary art. This contribution aims to measure the effects of this epochal transition on contemporary artistic practices, identifying and analyzing some specific cases in which the “things of the world” [Arendt 2017, p. 156] find new life in the digital dimension: George Legrady’s transformative machine (Pockets Full of Memories, 2001); Barbara Iweins’ photographic-archival obsession (Katalog, 2018-2022); Tarek Atoui’s performative Reverse Collection (2014); Antoni Abad’s participatory and digital archives (megafone.net, 2004; BLiND.wiki, 2015).